Equal opportunity and poverty reduction: how aid should be allocated? - Patrick Guillaumont; Phu Nguyen-Van; Thi Kim Cuong Pham; Laurent Wagner (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
This paper proposes a model of aid allocation which aims to equalize the opportunity between recipient countries to reduce the poverty. The model takes into account the natural growth deviation which is defined by the gap between the growth rate required to reach a development goal and the growth rate observed in the recipient countries. The resulting optimal aid allocation is computed using the estimation of a growth equation. Said equation includes effects of aid and structural handicaps to growth in recipient countries (which are represented by the economic vulnerability index and lack of human capital). To illustrate the interest of our approach, we perform a simulation which shows a substantial difference between the aid allocation obtained with our multi-criteria principle and the observed allocation. Moreover, we also shed light on the impact of the donors' sensitivity with respect to the natural growth deviation on the optimal aid allocation.
Keywords: D63; F35; I30; O19; 330; Efficiency; equity; development aid; growth deviation; vulnerability